Elites and Health Infrastructure Improvements in Industrializing Regimes - Tommy Krieger (Center for Economic Studies and ifo Institute (CESifo), 2022)
We collect information about more than 5,000 Prussian politicians, digitize administrative data on the provision of health-promoting public goods, and gather local-level information on workers' movements to study why elites in industrializing countries implement policies that improve the health of the poor. Exploiting county-level variation in elite structure, we present OLS and IV estimates, suggesting that elites improve access to health services due to pressure exerted by workers' movements and that they voluntarily implement policies that prevent disease outbreaks. An analysis of two rollcall votes substantiates the findings of the county-level analysis.
Keywords: H11; H42; H75; I15; N33; O43; P16; 330; distribution of power; elite structure; industrializing countries; political economy of health-promoting policies; Prussian history; redistribution; workers' movements